2022
DOI: 10.1186/s13019-022-01875-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following surgical repair of acute type A aortic dissection: a systematic review

Abstract: Background The outcomes of surgery for acute Stanford Type A aortic dissection (ATAAD) extend beyond mortality and morbidity. The aim of this systematic review was to summarise the literature surrounding health related quality of life (HR-QOL) following ATAAD, compare the outcomes to the standardised population, and to assess the impact of advanced age on HRQOL outcomes following surgery. Methods A systematic review of studies after January 2000 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…In line with the literature, our patients reported changes in daily life after aortic surgery [3]. There was a significant decline in physical fitness, with half of the respondents reporting a worsened state than that prior to surgery.…”
Section: Physical Functioningsupporting
confidence: 87%
See 2 more Smart Citations
“…In line with the literature, our patients reported changes in daily life after aortic surgery [3]. There was a significant decline in physical fitness, with half of the respondents reporting a worsened state than that prior to surgery.…”
Section: Physical Functioningsupporting
confidence: 87%
“…Cardiothoracic surgery studies and surveys-using the above-mentioned questionnaires-often do not use the endpoints/questions that are most meaningful to patients in their daily lives [3]. Unfortunately, the correlation between the lowest complication rates and the highest HRQoL are not always consistent [12].…”
Section: Patient Satisfaction and Measurement Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have compared short- and long-term postoperative surgical outcomes, such survival and complications, there are only a few studies in the literature that compares the postoperative QoL of the physical and psychological status after replacement of the AA [ 8 , 11 , 12 , 13 ]. Most available studies reported the outcome after acute type A dissection [ 14 , 15 , 16 , 17 ]. Some other studies have been performed after interventions of the descending and thoracoabdominal aorta [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, AD survivors still face many challenges, such as postoperative complications, impairment of physical function, decreased quality of life, and psychological trauma. [5][6][7][8] Therefore, the health promotion of AD is one of the important means to help them recover from the disease.…”
Section: Introductionmentioning
confidence: 99%